Cronología e interpretación de las acumulaciones holocenas de la val de las Lenas (Depresión del Ebro, Zaragoza) - Peña Monné, José Luis; Echeverría Arnedo, María Teresa; Petit-Maire, Nicole; Lafont, Raymond (Geographicalia, 2017)
The holocene accumulations on an infilled valley (val of the Ebro river basin have been studied, stablishing an evolution model satarting from the datings made C-14 and archaelogical data. The results obtained show the existence of two accumulative stages, one which begins at he Neolithic and another at the Iberian age, as well as one cutting phase along the last 1500 years.